2008
DOI: 10.1002/bdrb.20171
|View full text |Cite
|
Sign up to set email alerts
|

Lack of adaptive response of gamma radiation for protection against neutron‐induced teratogenesis

Abstract: Overall, this study shows that exposure to 0.3 Gy of gamma rays failed to induce an adaptive response of fetogenesis to a neutron challenge dose.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Recently, it was reported that in the adult mice, low‐dose low LET X‐rays could induce protective effects against the lethality caused by subsequent high doses from high LET heavy ion irradiations (Wang et al., ). On the other hand, a recent study in fetal mice showed no AR was observed when the priming dose was from gamma rays and challenge dose was mainly from neutron radiation (Lee et al., ). The present investigation is aimed to verify the possible existence of low LET X‐ray‐induced AR against the teratogenic effects from the challenge irradiations from high LET accelerated heavy ions in fetal mice and to explore its underlying mechanisms.…”
Section: Introductionmentioning
confidence: 97%
“…Recently, it was reported that in the adult mice, low‐dose low LET X‐rays could induce protective effects against the lethality caused by subsequent high doses from high LET heavy ion irradiations (Wang et al., ). On the other hand, a recent study in fetal mice showed no AR was observed when the priming dose was from gamma rays and challenge dose was mainly from neutron radiation (Lee et al., ). The present investigation is aimed to verify the possible existence of low LET X‐ray‐induced AR against the teratogenic effects from the challenge irradiations from high LET accelerated heavy ions in fetal mice and to explore its underlying mechanisms.…”
Section: Introductionmentioning
confidence: 97%
“…Interestingly, our previous work on verification of the protective efficacy from priming low-LET X-ray radiation against high-LET particle radiation in the same AR model in fetal mice also showed dependence of challenge radiation quality for successful AR induction, namely, the priming low-LET X-ray radiation could protect detrimental effect of challenge radiation from carbon-, neon-and silicon-particle radiation but not from iron-particle radiation (Wang et al, 2012). In addition, under the similar experimental setup, it was reported that the priming low-LET X-ray radiation did not protect neutronparticle radiation-induced teratogenesis (Lee et al, 2008). Why was no AR induced in the present work?…”
Section: Discussionmentioning
confidence: 86%